Biohydrogen - Pandey, Ashok (Elsevier Science & Technology, 2013)
This book provides in-depth information on basic and applied aspects of biohydrogen production. It begins with an introduction to the topic, and follows with the basic scientific aspects of biohydrogen production, such as the enzyme involved in biohydrogen production, the microorganisms and metabolic engineering information. It then provides state-of-art information on various aspects of biohydrogen production methods such as from solid wastes, from industrial effluents, thermo-chemical route for biohydrogen production, etc. It also includes information on engineering aspects such as the de.